1997
DOI: 10.2337/diacare.20.5.832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aspirin or Basic Amino Acids on Collagen Cross-Links and Complications in NIDDM

Abstract: It is concluded that 1) low-dose aspirin may reduce glycooxidative damage in people with NIDDM, and 2) treatment may need to continue for more than 1 year before clinical status improves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…It has been suggested that glycation of antioxidant enzymes due to hyperglycemia may be responsible for the reduction in GSHPx activity (Adachi et al, 1991;Wolff et al, 1991). It was suggested that low-dose ASA might reduce glycooxidative damage in diabetes (Contreras et al, 1997), mainly due to inhibition of post-Amadori Maillard reactions (a complex cascade of reactions initiated by glycation leading to production of "advanced glycation endproducts") (Hadley et al, 2001). In our experiment, we did not observe any hypoglycemic effect of the long-term ASA treatment (Table 1), but the ASA administration resulted in a slight decrease in the levels of glycated hemoglobin, presumably due to a competition between the two processes, protein glycosylation by a high glucose level and acetylation by ASA (Watala et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that glycation of antioxidant enzymes due to hyperglycemia may be responsible for the reduction in GSHPx activity (Adachi et al, 1991;Wolff et al, 1991). It was suggested that low-dose ASA might reduce glycooxidative damage in diabetes (Contreras et al, 1997), mainly due to inhibition of post-Amadori Maillard reactions (a complex cascade of reactions initiated by glycation leading to production of "advanced glycation endproducts") (Hadley et al, 2001). In our experiment, we did not observe any hypoglycemic effect of the long-term ASA treatment (Table 1), but the ASA administration resulted in a slight decrease in the levels of glycated hemoglobin, presumably due to a competition between the two processes, protein glycosylation by a high glucose level and acetylation by ASA (Watala et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which lysine inhibits nonenzymatic glycation seems to be related to its ability to combine with glucose and make the latter unavailable to react with protein lysine residues. However, L -lysine in combination with L -arginine treatment for 1 year did not prevent either skin collagen cross-linking or glycation in type 2 diabetic patients [19]. This discrepancy between animal and human data may be related to the dosage of L -lysine and the duration of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These include acetylsalicylic acid [12, 13, 14, 15, 16, 17, 18, 19], L -lysine [14, 20], D -lysine [21, 22, 23], L -arginine [24], vitamin C [20, 25, 26, 27, 28, 29], vitamin E [30], bendazac [31], and aminoguanidine [4, 5, 6, 7, 8, 9, 10, 32, 33]. Other novel therapeutic agents have been shown to improve albuminuria and mesangial expansion in diabetic mice [34, 35]and rats [36], with type 2 diabetes melllitus.…”
Section: Introductionmentioning
confidence: 99%
“…23,33,34 Different types of microvascular and microcirculatory damage is present [35][36][37] (eg, induced hyperviscosity and hypercoagulability, 13,33,[38][39][40] increased oxidative damage, 21,41 damage of vital enzymes and proteins by nonenzymatic glycosylation). 32,41,42 Sorbitol accumulates in the intracellular area because of glucose's increased polyol pathway activity, which causes cellular swelling and damage with osmotic effect. 20,21,43 Similar studies showed that effect in scanning electron microscopic studies.…”
Section: Diabetes Mellitus Detrimentally Affects a Random-patternmentioning
confidence: 99%